2019
DOI: 10.3389/fneur.2019.00579
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Rate Increases Around the Time of Cancer Diagnosis

Abstract: Objective: To test whether strokes increase around the time of cancer diagnosis, we comprehensively examined the correlations of cancer and stroke by employing a population-based cohort study design. Methods: One million people insured under the Taiwan's National Health Insurance program in 2005 were randomly sampled to create the study's dataset. According to the presence of cancer and/or stroke, patients were separated into cancer and stroke, cancer-only, and stroke-only gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 61 publications
2
24
0
2
Order By: Relevance
“…Next, we examined the frequency of ischaemic stroke adjusted by the number of cancer survivors. In accordance with the previous report, 17 the event rate of ischaemic stroke remained nested around the time of cancer diagnosis ( Supplementary Fig. 1B ).…”
Section: Resultssupporting
confidence: 93%
“…Next, we examined the frequency of ischaemic stroke adjusted by the number of cancer survivors. In accordance with the previous report, 17 the event rate of ischaemic stroke remained nested around the time of cancer diagnosis ( Supplementary Fig. 1B ).…”
Section: Resultssupporting
confidence: 93%
“…21,29 One study reported cancer types stratified by time after stroke and showed that esophageal cancer may be diagnosed later after stroke (mean, 2.3 years) than other cancer types (overall mean, 0.4 years). 35…”
Section: Diagnostic Interval Between Ischemic Stroke and New Cancermentioning
confidence: 99%
“…Our study focused on breast cancer and stroke and found that the time from the breast cancer diagnosis to the occurrence of stroke was approximately 6 years. According to Wei et al [18], the highest risk of stroke was found in patients with malignant brain tumors, followed by those with gastric cancer, prostate cancer, urogenital cancer, lung cancer, and leukemia. These cancer types conferred a higher risk of stroke than breast cancer, and their time from the diagnosis of cancer to the occurrence stroke was shorter.…”
Section: Breast Cancer and Strokementioning
confidence: 99%
“…Studies have shown that stroke occurs more frequently in cancer patients than in the general population and can present as the first sign of cancer, leading to its detection [17]. Wei et al [18] found that the risk of stroke was highest between 0.5 years before and after a diagnosis of cancer, with a steep-sided bell curve.…”
Section: Breast Cancer and Strokementioning
confidence: 99%